2006
DOI: 10.1038/sj.pcan.4500870
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic carcinosarcoma 15 years after combined external beam radiation and brachytherapy for prostatic adenocarcinoma: a case report

Abstract: A 65-year-old man with a history of combined pelvic external beam radiation therapy (EBRT) and brachytherapy for prostatic adenocarcinoma 15 years prior underwent total pelvic exenteration for presumed rectal sarcoma with prostatic invasion. Pathology revealed carcinosarcoma of prostatic origin. This patient exhibited the longest reported interval between initial presentation with prostatic adenocarcinoma and development of carcinosarcoma. This case is also the first reported case of prostatic carcinosarcoma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Since most prostate cancer-related deaths are due to metastases (911) it is of pivotal importance to understand how therapeutic intervention can influence metastatic development of irradiated cancer cells. Furthermore, cases of radiation-induced metastasis in prostate cancer patients have been reported (7477). Since clinical trials, using optimized settings for carbon ion treatment, have shown high survival rates and good local control (8,1215), carbon ion irradiation has been approved as a valid treatment for prostate cancers (8).…”
Section: Discussionmentioning
confidence: 99%
“…Since most prostate cancer-related deaths are due to metastases (911) it is of pivotal importance to understand how therapeutic intervention can influence metastatic development of irradiated cancer cells. Furthermore, cases of radiation-induced metastasis in prostate cancer patients have been reported (7477). Since clinical trials, using optimized settings for carbon ion treatment, have shown high survival rates and good local control (8,1215), carbon ion irradiation has been approved as a valid treatment for prostate cancers (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of cases have occurred after external beam radiotherapy [3, 16], only two previous cases of radiation-induced prostatic sarcoma after permanent brachytherapy are known [17, 18]. The latent periods were 8 and 9 years, and total RTx doses were 270 and 145 Gy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Current practice pattern may be also contributed to current finding. It was reported 50% of carcinosarcoma of the prostate cases were found in case of prostate adenocarcinoma previously treated with hormone or radiation therapy [4,7,24,25]. Re-biopsies are seldom performed in patients with prostate cancer, due to the perception that the re-biopsy of these patients in the face of known prostate cancer is not warranted, especially in the case of elderly patients with advance stage disease.…”
Section: Discussionmentioning
confidence: 99%